Molecular genetic heterogeneity in autosomal dominant drusen. Issue 6 (1st June 2001) - Tarttelin, Emma E; Gregory-Evans, Cheryl Y; Bird, Alan C; Weleber, Richard G; Klein, Michael L; Blackburn, James; Gregory-Evans, Kevin
Abstract : OBJECTIVE: Autosomal dominant drusen is of particular interest because of its phenotypic similarity to age related macular degeneration. Currently, mutation R345W of EFEMP1 and, in a single pedigree, linkage to chromosome 6q14 have been causally related to the disease. We proposed to investigate and quantify the roles of EFEMP1 and the 6q14 locus in dominant drusen patients from the UK and USA. DESIGN: Molecular genetic analysis. PARTICIPANTS: Ten unrelated families and 17 young drusen patients. MAIN OUTCOME MEASURES: Exons 1 and 2 of EFEMP1 were characterised by 5′ rapid amplification of cDNA ends and direct sequencing. Exons 1-12 of EFEMP1 were then investigated for mutation by direct sequencing. A Hpa II restriction digest test was constructed to detect the EFEMP1 R345W mutation. Marker loci spanning the two dominant drusen linked loci were used to generate haplotype data. RESULTS: Only seven of the 10 families (70%) and one of the 17 sporadic patients (6%) had the R345W mutation. The Hpa II restriction digest test was found to be a reliable and quick method for detecting this. No other exonic or splice site mutation was identified. Of the three families without EFEMP1 mutation, two were linked to the 2p16 region. CONCLUSIONS: EFEMP1 R345W accounts for only a proportion of the dominant drusen phenotype. Importantly, other families linked to chromosome 2p16 raise the possibility of EFEMP1 promoter sequence mutation or a second dominant drusen gene at this locus. Preliminary haplotype data suggest that the disease gene at the 6q14 locus is responsible for only a minority of dominant drusen cases.